URGICAL TREATMENT OF SOLID VARIANT OF PAPILLARY THYROID CARCINOMA: FIFTEEN-YEAR EXPERIENCE IN A TERTIARY CENTER : Treatment of solid variant of papillary thyroid carcinoma - Tausanovic, Katarina Milovan; Zivaljevic, Vladan; Stojanovic, Marina; Jovanovic, Milan; Stepanovic, Boban; Ilic, Jovan; Ivanis, Sara (Medical Research, 2024)
Aim: Papillary thyroid carcinoma (PTC) is a well differentiated, highly curable cancer, with a wide variety of histological forms. Although most of these variants are indolent, aggressive variants of PTC have been described. These variants include tall cell variant (TCV), hobnail variant (HV), columnar cell variant (CCV), diffuse sclerosing variant (DSV) and solid variant (SV). Solid variant represents one of the rarest forms of papillary thyroid carcinoma, with an incidence of about 2.6% according to retrospective studies.Methods: In this retrospective study, data of all patients that underwent thyroid surgery in our Clinic between January 2008 and January 2018 were analyzed. All relevant information was obtained from a prospectively maintained institutional database.Results: Of total of 1867 consecutive patients operated for follicular derived thyroid carcinomas during ten-year period, 38 had solid variant PTC as a definitive pathohistological finding (14 male and 24 female). The incidence of solid variant PTC is 2.04% in our series. Patient follow-up ranged from 36 to 168 months, disese specific five-year survival rate was 97.4%.Conclusion: Considering the scarcity of research discussing the prognosis of this variant of PTC, we believe that the treatment plan should be decided based on the extent of tumor and the experience of clinicians. WHO classification of thyroid neoplasms from 2022, may shed some light as to why the prognosis of solid variant PTC may be less aggressive than previously thought.